Analysing Students’ Critical Thinking Skills Through Solo Taxonomy in English Language Teaching: A Descriptive Study - Yossi Pranciska Ayu Citra; Ira maisarah (English Department, Faculty of Humanities, Udayana University, 2026)
The quality of education in Indonesia still faces many challenges. Based on the results of the Programme for International Student Assessment (PISA) showed that Indonesian students' competency in reading literacy, numeracy, and science is still below the average for OECD countries. These results indicate that most Indonesian students still struggle to apply basic concepts and solve problems that require higher-order thinking skills (HOTS). Therefore, the study aims to analyze Students’ Critical Thinking Skills level through SOLO Taxonomy in English Language Teaching. This study used a descriptive study design with a mixed-methods orientation. The data were collected through triangulation by involving performance tasks, observations, and interviews, and were analysed using both manual coding (Excel) and NVivo. This study's findings showed that most Indonesian students still struggle to reach higher cognitive levels. Specifically, 60% of the 18 students were at the multi-structural level (LOTS), and 40% of the 12 students succeeded in reaching the high-order thinking skill, which was at the Relational level. This study aims to make a contribution to English teachers, curriculum developers, and school administrators about students’ critical thinking skills level through SOLO Taxonomy in English language teaching. The findings may help educators design instructional activities that guide learners toward the highest level of critical thinking in the Extended Abstract level, where students can create, produce, generalize, and apply ideas across new contexts.